An Analysis of Moral and Patriotism Values in The Movie: Disney’s “The Little Mermaid” - Ema Sundari; Wanda Giovani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study analyzes moral values and patriotism in Disney's "The Little Mermaid" (2023) using descriptive qualitative methodology with content analysis techniques. The research addresses contemporary society's moral crisis and declining patriotic sentiment, particularly among younger generations, through examining how popular media can serve as educational vehicles for positive value transmission. Utilizing Magnis-Suseno's theoretical framework for moral values and Ginting's patriotism theory, the analysis identified five dominant moral values: courage, integrity, responsibility, cosmic awareness, and reconciliation, categorized across three human relationship dimensions. The patriotism analysis revealed four key values classified into blind and constructive patriotism, with constructive patriotism dominating 75% of examined scenes. Findings demonstrate that courage and integrity are the most prominent moral values, while pro-people leadership and multicultural unity represent significant patriotic elements. The research employed theory triangulation and data source triangulation to ensure validity. Results suggest that Disney's adaptation effectively integrates moral education and patriotic values relevant to Indonesia's contemporary challenges, including elite corruption and political polarization. This study contributes to educational literature by demonstrating how modern film adaptations can serve as meaningful resources for character development and nationalism education.